Dual catalyst system composed by nickel and vanadium complexes containing nitrogen ligands for ethylene polymerization - Furlan,Luciano G. (2005)
Branched polyethylene/high-density polyethylene blends (BPE/HDPE) were prepared using the combined [NiCl2(alpha-diimine)] (1) (alpha-diimine = 1,4-bis(2,6-diisopropylphenyl)-acenaphthenediimine) and [TpMs*VCl2(NtBu)] (2) (TpMs* = hydridobis(3-mesitylpyrazol-1-yl)(5-mesitylpyrazol-1-yl)) catalysts. The polymerization reactions were performed in hexane or toluene at three different polymerization temperatures (0, 30 and 50 °C) and several nickel molar fractions (xNi), using MAO as cocatalyst. At all temperatures, the activities show an approximate linear correlation with xNi, indicating a non-synergistic effect between the nickel and the vanadium species. Higher activities were found in toluene at 0 °C. The melting temperatures for the polyethylene blends produced at 0 °C decrease as xNi increases in the medium indicating good miscibility between the polyethylene phases made by both catalysts. The surface morphology of the BPE/HDPE blends studied by scanning electron microscopy (SEM) revealed low miscibility between the PE phases mainly in the case of the polymer blends produced at high temperature (50 ºC).